2017
DOI: 10.1101/cshperspect.a029736
|View full text |Cite
|
Sign up to set email alerts
|

On the Run for Hippocampal Plasticity

Abstract: Accumulating research in rodents and humans indicates that exercise benefits brain function and may prevent or delay onset of neurodegenerative conditions. In particular, exercise modifies the structure and function of the hippocampus, a brain area important for learning and memory. This review addresses the central and peripheral mechanisms underlying the beneficial effects of exercise on the hippocampus. We focus on running-induced changes in adult hippocampal neurogenesis, neural circuitry, neurotrophins, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 468 publications
5
75
0
1
Order By: Relevance
“…Evidence from human and animal studies has established that regular aerobic exercise can improve cognitive performance and can protect against anxiety and depression 18,19 . Cognitive challenges performed during exercise result in levels of enhancement of synaptic plasticity, as well as learning and memory, greater than either challenge alone 20 .…”
Section: Neuronal Adaptations To Imsmentioning
confidence: 99%
“…Evidence from human and animal studies has established that regular aerobic exercise can improve cognitive performance and can protect against anxiety and depression 18,19 . Cognitive challenges performed during exercise result in levels of enhancement of synaptic plasticity, as well as learning and memory, greater than either challenge alone 20 .…”
Section: Neuronal Adaptations To Imsmentioning
confidence: 99%
“…The p75 is a member of the TNF receptor superfamily that can bind to BDNF and transmits signals important for determining which neurons survive during development (Huang and Reichardt, 2001). At present, the precise molecular mechanisms regarding exercisemediated neurogenesis are still not fully known (Baptista and Andrade, 2018;Cooper et al, 2018). Importantly, BDNF is a candidate mechanism underlying these exercise-induced benefits that help optimize brain plasticity outcomes via exercise intervention (Baptista and Andrade, 2018;Cooper et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the precise molecular mechanisms regarding exercisemediated neurogenesis are still not fully known (Baptista and Andrade, 2018;Cooper et al, 2018). Importantly, BDNF is a candidate mechanism underlying these exercise-induced benefits that help optimize brain plasticity outcomes via exercise intervention (Baptista and Andrade, 2018;Cooper et al, 2018). Acute high-intensity exercise increases the expression of BDNF (Venezia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is generally considered beneficial for brain health and cognitive function in normal subjects. Exercising implicates positive effects for the nervous tissue, such as increased blood flow, increased synapse plasticity and increased neurogenesis, particularly in the hippocampus (Cooper et al, 2018). Several studies have shown that exercise promotes the recovery of the hippocampal function after various forms of neural insult (Kim et al, 2011;Cechetti et al, 2012;Winocur et al, 2014;Klein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%